Photogrammetric Facial Analysis of Rhinoplasty Applicants in Shiraz - Ostovari, Mohsen; Fazelzadeh, Afsoon; Faraz, Mehdi; Mehdizadeh, Alireza; Mohebbi, Zinat (Journal of Otorhinolaryngology and Facial Plastic Surgery, 2021)
Background: Nose shape plays an important role in individuals’ facial appearance and its morphology depends on ethnicity, gender, and environmental conditions. Identifying nasal problems and measuring landmarks can lead to making a perfect surgery plan through preoperative image analysis. Methods: In this study, a photogrammetric analysis was performed on 120 female rhinoplasty applicants, aged 18-30 in Shiraz, Iran. Recorded parameters are nasal height and width, nasolabial and nasofrontal angle. Nasal indices were calculated according to heights and widths of noses. Also, facial asymmetry and nose hump checked for every patient. Results: Measurements showed that the average nasal index was 67.15 ± 4.72. Thus, the nose of rhinoplasty applicants was the leptorrhine type. Furthermore, the average nasofrontal and nasolabial angles were 145.22° ± 9.93°and 94.47° ± 14.25°. Among all applicants, 35 percent have an asymmetric nose and 31 percent have a nose hump. Conclusion: An accurate facial analysis of rhinoplasty applicants was performed in this study, and the resultant facial profiles can be used in nose surgery planning and in further ethnic research.